Going from the talk to doing the walk: extending Malaysian public sector transparency - Abu Bakar, Nur Barizah; Mohamad, Muslim Har Sani (2009)
The most recent Malaysian general election held in 2007 saw an unprecedented result which denied the ruling coalition, the National Front (BN) a two-thirds majority which it had enjoyed for the last 50 years. More specifically, the election results has allowed for the first time in the history of Malaysian politics, the Opposition front comprising three parties to capture five key states in the Malaysian Peninsula to form the State Governments and collectively, the three Opposition parties captured 10 out of 11 parliamentary constituencies in the capital city of Kuala Lumpur. Political analysts and observers locally and globally have attributed this swing in votes partly to the public call for change towards a more transparent and accountable government through having a stronger opposition in the Malaysian democratic process. Besides, the postmortem done by the ruling government has also found similar reasons among others.